Measuring disincentives to formal work - Michael Weber (IZA World of Labor, 2015)
Evidence from transition economies shows that formal work may not pay, particularly for low-wage earners. Synthetic measurements of work disincentives, such as the formalization tax rate or the marginal effective tax rate, confirm a significant positive correlation between these measurements and the probability of informal work. These measures are especially informative for impacts at lower wage levels, where informality is highest. Policymakers who want to increase formal work can use these measurements to determine optimal labor taxation rates for low-wage earners and reform benefit design.
Keywords: H26; J32; O17; 330; informal employment; synthetic measurements; tax wedge; tax evasion; formalization tax rate; marginal effective tax rate